A method for etching nano-patterns of thick film materials
Through the nano-pattern etching method of thick film materials, the problem of difficulty in processing and etching of graphene nano-films of tens of nanometers in the prior art is solved, and high-precision nano-order etching and material performance improvement are achieved.
Patent Information
- Application Number
- CN202210225160.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-09
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-03-09
AI Technical Summary
The prior art is difficult to effectively process and etch graphene nanofilms with a thickness of tens of nanometers, resulting in low light absorption and inability to prepare large areas.
The nano-pattern etching method of thick film material was used to form an inverted trapezoidal structure by spin-coating electron beam glues AR-P 669.04 and AR-P 679.03, and combined with electron beam lithography and surface electron beam evaporation aluminum film, followed by acetone peeling and ICP etching technology, and finally, the aluminum film was removed with chlorine at 200°C to achieve high-precision etching of thicker graphene nanofilms.
Nanoscale pattern etching of film materials with a thickness of tens of nanometers is achieved, the light absorption rate and carrier concentration of graphene films are improved, the advantages of infrared plasmons are enhanced, and the quality of the material is ensured that there are no additional defects introduced.
Smart Images

Figure CN114604820B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of nano-pattern etching, and relates to a preparation method of undoped and doped macroscopically assembled graphene nano-films, and a nano-pattern etching method of such nano-films with different thicknesses on different substrates. Background Art
[0002] With the development of technology, nanomaterials with a large surface area to volume ratio, such as nanowires, nanotubes and nanobelts, have very obvious advantages in electrical, optical, chemical and biosensor applications compared to bulk materials. At present, the processing of nanomaterials is mainly divided into bottom-up and top-down processing techniques. The bottom-up processing technique has poor controllability in terms of the orientation of nanostructure growth, and needs to rely on a certain substrate, and cannot be directly processed on the required device. For example, the chemical vapor deposition method requires first performing graphic etching on a copper or nickel substrate, growing materials on this basis, and finally transferring them through traditional methods. In addition to the very complicated process, the structure prepared by this method has a large line width, and it is difficult to achieve nanometer-level etching. Top-down processing methods are commonly used for nanoimprinting and electron beam lithography, but this method is mostly based on single-layer or cover-layer thin film materials, and is not applicable to thin film materials with a thickness of tens of nanometers.
[0003] To this end, we have designed a thick film material pattern etching technology, and invented a method for preparing macroscopically assembled intrinsic graphene nanofilms and macroscopically assembled graphene nanofilms doped with bromine, molybdenum chloride, copper chloride, and molybdenum disulfide by gas-assisted exfoliation. By increasing the thickness, the light absorption of the film is greatly increased, overcoming the problems of low light absorption rate and inability to prepare large areas in traditional graphene. In addition, by doping the graphene film, the carrier concentration of the graphene film can be increased, further increasing the advantages of mid-infrared plasmons such as graphene. Summary of the invention
[0004] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a method for etching nano-patterns of thick film materials.
[0005] The purpose of the present invention is achieved through the following technical solutions: a method for etching nano-patterns of thick film materials, which can pattern thin films with a thickness of tens of nanometers. The EBL glue uses two layers of AR-P 679.03 and AR-P 669.04, and forms an inverted trapezoidal structure after exposure, which effectively solves the problem of the subsequent metal stripping process being too narrow to be stripped. In addition, the surface electron beam evaporates the metal aluminum film to protect the thin film material, and the material properties do not change during the ICP process. Finally, chlorine gas is passed through at 200°C to remove the surface aluminum, effectively avoiding the problem of nanostructures falling off from the substrate due to wet etching. This etching technology can achieve the etching of thicker thin film materials while ensuring that the material does not introduce additional defect states. The specific steps are as follows:
[0006] (1) Transferring the thin film material to the substrate;
[0007] (2) Spin coating AR-P 669.04, 600r 10s + 6000r 60s, then bake in an oven at 150°C for 1h, then spin coating AR-P 679.03, 600r 10s + 6000r 60s, then bake on a hot plate at 150°C for 3min; after exposure, an inverted trapezoidal structure is formed;
[0008] (3) performing electron beam lithography on the spin-coated thin film material;
[0009] (4) Electron beam evaporation of aluminum film on the surface of the photolithography pattern, the thickness of the aluminum film is 50nm;
[0010] (5) Acetone stripping to remove the aluminum with electron beam glue, followed by ICP etching;
[0011] (6) At 200°C, chlorine gas is used to remove the surface electron beam evaporated aluminum film to obtain the etched film structure.
[0012] Furthermore, the film thickness is several tens of nanometers.
[0013] Furthermore, in step 1, the film material is a macroscopically assembled graphene nanofilm; or a macroscopically assembled graphene nanofilm doped with bromine, molybdenum chloride, copper chloride, or molybdenum disulfide; and the substrate comprises: a semiconductor, glass, or a polymer.
[0014] Furthermore, in step (3), the minimum line width of the electron beam lithography pattern is 100 nm.
[0015] Furthermore, the specific steps of preparing the macroscopically assembled graphene nanofilm are as follows:
[0016] (1) Graphene oxide films were obtained by filtration on AAO substrates, with film thicknesses of 60 nm, 90 nm, 120 nm, 150 nm, and 180 nm;
[0017] (2) The AAO+GO film is placed in a cavity with HI vapor for chemical reduction, the heat source is an oil bath or a water bath with a temperature of 80-120 degrees Celsius, after reduction, the graphene oxide is automatically peeled off from the substrate, and the concentration of HI in the cavity is above 0.3g / L, and the concentration of water vapor is below 0.07g / L. The cavity is a closed cavity, containing a hydroiodic acid solution, and the top of the cavity has a water absorption area; and the lower part of the cavity is placed in the heat source; a carrier is provided in the cavity above the liquid level of the hydroiodic acid solution, for loading the substrate of the graphene oxide nanofilm; the carrier is a polytetrafluoroethylene grid or a hollow glass rack.
[0018] (3) The exfoliated graphene oxide film is placed in a graphite furnace to prepare graphene films with thicknesses of 20 nm, 30 nm, 40 nm, 50 nm and 60 nm. The sintering time is 4 hours and the temperature range is 1300°C-3000°C.
[0019] Furthermore, the specific steps for preparing the bromine-doped macroscopically assembled graphene nanofilm are as follows:
[0020] (1) transferring the prepared macroscopically assembled graphene nanofilm to a semiconductor substrate;
[0021] (2) Add 5 ml of liquid bromine to the semiconductor substrate with the macroscopically assembled graphene thin nanofilm on the surface and dope it at room temperature for 24 hours.
[0022] Furthermore, the specific steps for preparing the molybdenum chloride doped macroscopically assembled graphene nanofilm are as follows:
[0023] (1) transferring the prepared macroscopically assembled graphene nanofilm to a semiconductor substrate;
[0024] (2) Adding molybdenum chloride and molybdenum oxide to a semiconductor substrate having a macroscopically assembled graphene thin nanofilm on its surface, and calcining at 300 degrees in vacuum for 24 hours.
[0025] Furthermore, the specific steps for preparing the cupric chloride doped macroscopically assembled graphene nanofilm are as follows:
[0026] (1) transferring the prepared macroscopically assembled graphene nanofilm to a semiconductor substrate;
[0027] (2) Adding copper chloride to the environment of a semiconductor substrate with a macroscopically assembled graphene thin nanofilm on the surface, and calcining at 300 degrees in vacuum for 24 hours.
[0028] The beneficial effects of the present invention are as follows: the preparation steps of the macroscopically assembled nanofilm are concise, and the operation is simple, cheap and short; and this method does not require a transfer agent, thereby avoiding the problem that the strength of the AAO film is insufficient to bear the weight of the transfer agent after the size of the nanofilm increases and the difficulty of transfer operation during the solid-phase transfer process, thereby ensuring the integrity of the large-size film; in addition, the complete penetration of hydrogen iodide during the reduction process avoids the uneven reduction during the solid-phase transfer method and the tearing effect of the contraction of the solid-phase transfer agent on the film, thereby further ensuring the uniformity of the nanofilm.
[0029] Doping macroscopically assembled nanofilms can increase the carrier concentration of graphene films, increase the carrier concentration in heterojunctions, and increase the advantages of infrared plasmons in graphene.
[0030] The nano-patterning etching technology for thick film materials can achieve patterning of thin film materials with a thickness of tens of nanometers and a line width of nanometers while ensuring the quality of the material without introducing additional defects. In addition, the unique properties of the material can effectively increase the resonant absorption of the material in the mid-infrared plasmon. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 Schematic diagram of the etching steps for thick film materials.
[0032] Figure 2 This is the graphic etching result of the intrinsic macroscopically assembled graphene film with a thickness of 20 nm and a line width of 100 nm prepared in Example 1.
[0033] Figure 3 This is the graphic etching result of the bromine-doped macroscopic assembled graphene film with a thickness of 30 nm and a line width of 100 nm prepared in Example 2.
[0034] Figure 4 This is the graphic etching result of the macroscopic assembled graphene doped with molybdenum chloride prepared in Example 3 with a thickness of 40 nm and a line width of 100 nm.
[0035] Figure 5 This is the graphic etching result of the copper chloride-doped macro-assembled graphene film with a thickness of 50 nm and a line width of 100 nm prepared in Example 4.
[0036] Figure 6 This is the graphic etching result of the macroscopic assembled graphene 60nm thick film doped with molybdenum disulfide prepared in Example 5 and with a line width of 100nm. DETAILED DESCRIPTION
[0037] The specific implementation modes of the present invention are further described in detail below with reference to the accompanying drawings.
[0038] like Figure 1As shown, the present invention provides a method for etching nano-patterns of thick film materials, which can be used for patterning thin films with a thickness of tens of nanometers. The EBL glue uses two layers of AR-P 679.03 and AR-P 669.04, and forms an inverted trapezoidal structure after exposure, which effectively solves the problem of the subsequent metal stripping process being too narrow to be stripped. In addition, the surface electron beam evaporates the metal aluminum film to protect the thin film material, and the material properties do not change during the ICP process. Finally, chlorine gas is passed through at 200°C to remove the surface aluminum, effectively avoiding the problem of nanostructures falling off from the substrate due to wet etching. This etching technology can achieve the etching of thicker thin film materials while ensuring that the material does not introduce additional defect states. The specific steps are as follows:
[0039] (1) Transferring a thin film material onto a substrate; the thin film material is a macroscopically assembled graphene nanofilm; or a macroscopically assembled graphene nanofilm doped with bromine, molybdenum chloride, copper chloride, or molybdenum disulfide; the substrate comprises: a semiconductor, glass, or a polymer. Specifically, the following four situations are included:
[0040] A. The specific steps of preparing the macroscopically assembled graphene nanofilm are as follows:
[0041] (a) Graphene oxide films were obtained by filtration on AAO substrates with film thicknesses of 60 nm, 90 nm, 120 nm, 150 nm, and 180 nm;
[0042] (b) The AAO+GO film is placed in a cavity with HI vapor for chemical reduction, the heat source is an oil bath or a water bath with a temperature of 80-120 degrees Celsius, after reduction, the graphene oxide is automatically peeled off from the substrate, in the cavity, the concentration of HI is above 0.3g / L, and the concentration of water vapor is below 0.07g / L. The cavity is a closed cavity, filled with a hydroiodic acid solution with a purity of 55.0-58.0%, and the top of the cavity has a water absorption area; and the lower part of the cavity is placed in the heat source; a carrier is provided in the cavity above the liquid level of the hydroiodic acid solution for loading the substrate of the graphene oxide nanofilm; the carrier is a polytetrafluoroethylene grid or a hollow glass rack.
[0043] (c) The exfoliated graphene oxide film was placed in a graphite furnace to prepare graphene films with thicknesses of 20 nm, 30 nm, 40 nm, 50 nm and 60 nm. The sintering time was 4 hours and the temperature range was 1300°C-3000°C.
[0044] B. The specific steps for preparing the bromine-doped macroscopically assembled graphene nanofilm are as follows:
[0045] (a) Transferring the prepared macroscopically assembled graphene nanofilm to a semiconductor substrate;
[0046] (b) Add 5 ml of liquid bromine to the semiconductor substrate with macroscopically assembled graphene thin nanofilm on the surface and dope it at room temperature for 24 hours.
[0047] C. The specific steps for preparing the molybdenum chloride doped macroscopically assembled graphene nanofilm are as follows:
[0048] (a) Transferring the prepared macroscopically assembled graphene nanofilm to a semiconductor substrate;
[0049] (b) Molybdenum chloride and molybdenum oxide are added to the environment of a semiconductor substrate with a macroscopically assembled graphene thin nanofilm on the surface, and calcined at 300 degrees in vacuum for 24 hours.
[0050] D. The specific steps for preparing the copper chloride doped macroscopically assembled graphene nanofilm are as follows:
[0051] (a) Transferring the prepared macroscopically assembled graphene nanofilm to a semiconductor substrate;
[0052] (b) Add copper chloride to the environment of a semiconductor substrate with a macroscopically assembled graphene thin nanofilm on its surface, and calcine it at 300 degrees in vacuum for 24 hours.
[0053] (2) Spin coating AR-P 669.04, 600r 10s + 6000r 60s, then bake in an oven at 150°C for 1h, then spin coating AR-P 679.03, 600r 10s + 6000r 60s, then bake on a hot plate at 150°C for 3min; after exposure, an inverted trapezoidal structure is formed;
[0054] (3) performing electron beam lithography on the spin-coated thin film material;
[0055] (4) Electron beam evaporation of aluminum film on the surface of the photolithography pattern, the thickness of the aluminum film is 50nm;
[0056] (5) Acetone stripping to remove the aluminum with electron beam glue, followed by ICP etching;
[0057] (6) At 200°C, chlorine gas is used to remove the surface electron beam evaporated aluminum film to obtain the etched film structure.
[0058] Embodiment 1:
[0059] The intrinsic macroscopically assembled graphene 20nm thick film was transferred to a silicon substrate, and electron beam glue AR-P669.04 was spin-coated, 600r 10s+6000r 60s, and then baked in an oven at 150℃ for 1h. Then AR-P 679.03 was spin-coated, 600r10s+6000r 60s, and then baked on a hot plate at 150℃ for 3min. The electron beam exposure lithography pattern was obtained, and the pattern line width was 100nm. After development, 50nm aluminum was evaporated on the surface by electron beam evaporation, and acetone was peeled off to remove the aluminum in the electron beam glue part. The macroscopically assembled graphene nanofilm without aluminum film protection was etched by ICP. Finally, chlorine gas was passed at a high temperature of 200℃ to remove the aluminum film covering the surface of the film, and a 20nm thick intrinsic macroscopically assembled graphene film array pattern with a line width of 100nm was obtained. The results are shown in FIG. Figure 2 shown.
[0060] Embodiment 2:
[0061] The bromine-doped macro-assembled graphene 30nm thick film was transferred to a germanium substrate, and electron beam glue AR-P669.04 was spin-coated, 600r 10s+6000r 60s, and then baked in an oven at 150℃ for 1h. AR-P 679.03 was spin-coated, 600r10s+6000r60s, and then baked on a hot plate at 150℃ for 3min. Electron beam exposure was performed, and the pattern line width was 100nm. After development, 50nm aluminum was evaporated on the surface by electron beam evaporation, and acetone was peeled off to remove the aluminum in the electron beam glue part. The macro-assembled graphene nanofilm without aluminum film protection was etched by ICP. Finally, chlorine gas was passed at a high temperature of 200℃ to remove the aluminum film covering the surface of the film, and an array pattern of bromine-doped macro-assembled graphene 30nm thick film with a line width of 100nm was obtained. The results are shown in FIG. Figure 3 shown.
[0062] Embodiment 3:
[0063] The 40nm thick film of macroscopically assembled graphene doped with molybdenum chloride was transferred to a PDMS flexible substrate, and electron beam glue AR-P 669.04 was spin-coated at 600r for 10s and 6000r for 60s, and then baked in an oven at 150°C for 1h. Then AR-P 679.03 was spin-coated at 600r for 10s and 6000r for 60s, and then baked on a hot plate at 150°C for 3min. Electron beam exposure was performed, and the line width of the pattern was 100nm. After development, 50nm aluminum was evaporated on the surface by electron beam evaporation, and acetone was peeled off to remove the aluminum in the part with electron beam glue. The macroscopically assembled graphene nanofilm without aluminum film protection was etched by ICP. Finally, chlorine gas was passed at a high temperature of 200°C to remove the aluminum film covering the surface of the film, and an array pattern of a 40nm thick film of macroscopically assembled graphene doped with molybdenum chloride with a line width of 100nm was obtained. The results are shown in FIG. Figure 4 shown.
[0064] Embodiment 4:
[0065] The 50nm thick film of macroscopically assembled graphene doped with copper chloride was transferred to an InP substrate, and electron beam glue AR-P 669.04 was spin-coated, 600r 10s+6000r 60s, and then baked in an oven at 150℃ for 1h. Then AR-P 679.03 was spin-coated, 600r 10s+6000r60s, and then baked on a hot plate at 150℃ for 3min. Electron beam exposure was performed, and the line width of the pattern was 100nm. After development, 50nm aluminum was evaporated on the surface by electron beam evaporation, and acetone was peeled off to remove the aluminum in the part with electron beam glue. The macroscopically assembled graphene nanofilm without aluminum film protection was etched by ICP. Finally, chlorine gas was passed at a high temperature of 200℃ to remove the aluminum film covering the surface of the film, and an array pattern of a 50nm thick film of macroscopically assembled graphene doped with copper chloride with a line width of 100nm was obtained. The results are shown in FIG. Figure 5 shown.
[0066] Embodiment 5:
[0067] The 60nm thick film of macroscopically assembled graphene doped with molybdenum disulfide was transferred to a glass substrate, and electron beam glue was spin-coated. The pattern line width was 100nm. After development, 50nm aluminum was evaporated on the surface by electron beam evaporation. Acetone was peeled off to remove the aluminum in the part with electron beam glue. The macroscopically assembled graphene nanofilm without aluminum film protection was etched by ICP. Finally, chlorine gas was passed at a high temperature of 200℃ to remove the aluminum film covering the surface of the film, and an array pattern of a 60nm thick film of macroscopically assembled graphene doped with molybdenum disulfide with a line width of 100nm was obtained. The results are shown in FIG. Figure 6 shown.
[0068] The above embodiments are used to illustrate the present invention rather than to limit the present invention. Any modification and change made to the present invention within the spirit of the present invention and the protection scope of the claims shall fall within the protection scope of the present invention.
Claims
1. A method for etching nanopatterns of thick film materials, characterized in that: The specific steps are as follows: (1) Transferring a thin film material onto a substrate; the thin film material is a macroscopically assembled graphene nanofilm; or a macroscopically assembled graphene nanofilm doped with bromine, molybdenum chloride, copper chloride or molybdenum disulfide; the substrate comprises: a semiconductor, glass or a polymer; (2) Spin-coat AR-P 669.04, 600r 10s + 6000r 60s, then bake in an oven at 150°C for 1h, then spin-coat AR-P679.03, 600r 10s + 6000r 60s, then bake on a hot plate at 150°C for 3min; after exposure, an inverted trapezoidal structure is formed, which is conducive to the subsequent metal stripping process; (3) Electron beam lithography is performed on the spin-coated thin film material, and the minimum line width of the electron beam lithography pattern is 100 nm; (4) Electron beam evaporation of aluminum film on the surface of the photolithography pattern, with a thickness of 50 nm; (5) Acetone stripping to remove the aluminum with electron beam glue, followed by ICP etching; (6) At 200°C, chlorine gas was used to remove the electron beam evaporated aluminum film on the surface to obtain an etched film structure with a film thickness of several tens of nanometers and a line width of 100 nanometers for the film array pattern.
2. The thick film material pattern etching method according to claim 1, characterized in that: The specific steps of preparing the macroscopically assembled graphene nanofilm are as follows: (1) Graphene oxide films were obtained by filtration on AAO substrates, with film thicknesses of 60nm, 90nm, 120nm, 150nm, and 180nm respectively; (2) Placing the AAO+GO film in a chamber with HI vapor for chemical reduction, wherein the heat source is an oil bath or a water bath at a temperature of 80-120 degrees Celsius. After reduction, the graphene oxide is automatically peeled off from the substrate. In the chamber, the concentration of HI is above 0.3 g / L and the concentration of water vapor is below 0.07 g / L. The chamber is a closed chamber containing a hydroiodic acid solution, and the top of the chamber has a water absorption area. The lower part of the chamber is placed in the heat source. A carrier is provided in the chamber above the liquid level of the hydroiodic acid solution for loading the substrate of the graphene oxide nanofilm. The carrier is a polytetrafluoroethylene grid or a hollow glass rack. (3) The exfoliated graphene oxide film was placed in a graphite furnace to prepare graphene films with thicknesses of 20 nm, 30 nm, 40 nm, 50 nm and 60 nm. The sintering time was 4 hours and the temperature range was 1300°C-3000°C.
3. The thick film material pattern etching method according to claim 2, characterized in that: The specific steps of preparing the bromine-doped macroscopically assembled graphene nanofilm are as follows: (1) Transferring the prepared macroscopically assembled graphene nanofilm to a semiconductor substrate; (2) Add 5 ml of liquid bromine to the semiconductor substrate with macroscopically assembled graphene thin nanofilm on the surface and dope it at room temperature for 24 hours.
4. The thick film material pattern etching method according to claim 2, characterized in that: The specific steps of preparing the molybdenum chloride doped macroscopically assembled graphene nanofilm are as follows: (1) Transferring the prepared macroscopically assembled graphene nanofilm to a semiconductor substrate; (2) Add molybdenum chloride and molybdenum oxide to a semiconductor substrate having a macroscopically assembled graphene thin nanofilm on its surface, and calcine at 300 degrees in vacuum for 24 hours.
5. The thick film material pattern etching method according to claim 2, characterized in that: The specific steps of preparing the cupric chloride doped macroscopically assembled graphene nanofilm are as follows: (1) Transferring the prepared macroscopically assembled graphene nanofilm to a semiconductor substrate; (2) Add copper chloride to the environment of a semiconductor substrate with a macroscopically assembled graphene thin nanofilm on the surface, and calcine it at 300 degrees in vacuum for 24 hours.
Citation Information
Patent Citations
Method for producing nano-dimension metal structure overlapped by metal membrane in large area
CN101470355A
High-conductivity graphene fiber and preparation method thereof
CN105544017A